1993
DOI: 10.1016/0378-1097(93)90259-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Legionella pneumophila in biofilms containing a complex microbial consortium by gas chromatography-mass spectrometry analysis of genus-specific hydroxy fatty acids

Abstract: A gas chromatographic-mass spectrometric method was used to detect Legionella pneumophila in biofilms in potable water containing a complex microbial consortium. The unique 3-hydroxy and 2,3-dihydroxy fatty acids of the L. pneumophila lipopolysaccharides (LPS) were detected in both the planktonic phase of the continuous culture model and in the biofilms forming on both copper and polyethylene substrata. The technique confirmed that lower numbers of Legionella colonised and grew on copper in comparison to polye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
1
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 10 publications
1
16
1
3
Order By: Relevance
“…The bacteria are more easily detected from swab samples of biofilm than from flowing water, suggesting that the majority of the legionellae are biofilm associated (235). A limited number of studies have attempted to characterize the bacteria's interaction within these complex ecosystems (236,237,282). These studies have evaluated the effect of temperature and surface materials on the growth of L. pneumophila as well as the effect of biocides on sessile legionellae.…”
Section: Association With Biofilmsmentioning
confidence: 99%
“…The bacteria are more easily detected from swab samples of biofilm than from flowing water, suggesting that the majority of the legionellae are biofilm associated (235). A limited number of studies have attempted to characterize the bacteria's interaction within these complex ecosystems (236,237,282). These studies have evaluated the effect of temperature and surface materials on the growth of L. pneumophila as well as the effect of biocides on sessile legionellae.…”
Section: Association With Biofilmsmentioning
confidence: 99%
“…The direct¯uorescent antibody technique has proved to be very useful for detecting L. pneumophila in natural aquatic systems (Fliermans et al, 1981;Alary and Joly, 1992). A gas chromatographic± mass spectrometric method, based on unique 3-hydroxy and 2,3-dihydroxy fatty acids of the L. pneumophila lipopolysaccharides, has been used to detect L. pneumophila in bio®lms in potable water containing a complex microbial consortium (Walker et al, 1993). Various molecular methods have also been developed for detecting Legionella.…”
Section: Detection and Disinfectionmentioning
confidence: 99%
“…Opportunistic pathogens that have been isolated from biofilms in potable water systems include Mycobacterium avium, Pseudomonas aeruginosa, Klebsiella spp., Legionella spp., and Flavobacterium spp. (29,39,50). Payment et al (31) suggested that approximately 35% of gastrointestinal infections could be associated with the consumption of apparently potable water.…”
mentioning
confidence: 99%